Genome-wide identification, characterization of RLR genes in Yesso scallop (Patinopecten yessoensis) and functional regulations in responses to ocean acidification. Issue 98 (March 2020) - Zhu, Xinghai; Liao, Huan; Yang, Zujing; Peng, Cheng; Lu, Wei; Xing, Qiang; Huang, Xiaoting; Hu, Jingjie; Bao, Zhenmin
Abstract: Retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs), are crucial sensors with a conserved structure in cytoplasm, inducing the production of cytokines, chemokines and host restriction factors which mediate a variety of intracellular activities to interfere with distinct PAMPs (pathogen-associated molecular patterns) for eliminating pathogens in innate immune system. Although RLR genes have been investigated in most vertebrates and some invertebrates, the systematic identification and characterization of RLR genes have not been reported in scallops. In this study, four RLR genes ( PY-10413.4, PY-10413.5, PY-443.7 and PY-443.8, designated PyRLRs ) were identified in Yesso scallop ( Patinopecten yessoensis ) through whole-genome scanning through in silico analysis, including two pairs of tandem duplicate genes located on the same scaffold ( PY-10413.4 and PY-10413.5, PY-443.7 and PY-443.8, respectively). Phylogenetic and protein structural analyses were performed to determine the identities and evolutionary relationships of these genes. The expression profiles of PyRLRs were determined in all developmental stages, in healthy adult tissues, and in mantles that simulated ocean acidification (OA) exposure (pH = 6.5 and 7.5) at different time points (3, 6, 12 and 24 h). Spatiotemporal expression patterns suggested the functional roles of PyRLRs in all stages of development and growth of the scallop. Regulation expressions revealed PY-10413.4 and PY-10413.5 with one or two CARD(s) (caspase activation and recruitment domain) were up-regulated expressed at most time points, whereas PY-443.8 and PY-10413.4 without CARD were significantly down-regulated at each time points, suggesting functional differentiations in the two pairs of PyRLRs based on the structural differences in response to OA. Collectively, this study demonstrated gene duplication of RLR family genes and provide primary analysis for versatile roles in the response of the bivalve innate immune system to OA challenge. Highlights: Four RLR family members were identified in Patinopecten yessoensis genome. Phylogenetic analysis confirmed duplication and evolutionary relationship of PyRLRs. Spatiotemporal expression patterns suggested the functional roles of PyRLRs. Constitutive and inducible divergence of PyRLRs has been arisen to the immune stress. The four PyRLRs showed functional differentiations in response to OA.